MEMBANGKITKAN SELF AWARENESS IN MARRIAGE MELALUI LAYANAN INFORMASI DENGAN PENDEKATAN PSIKOLOGI PERKAWINAN - Hasneli, Hasneli; Aulia, Rahmadianti; Alfaiz, Alfaiz (Jurnal Terapan Abdimas, 2022)
Abstract. Providing information services on the psychology of marriage to course participants as prospective brides in the KUA District of Lubuk Kilangan Padang City, this is based on the phenomenon of a fairly high marriage rate, namely 40 pairs per month, and indications of divorce each year reaching 100 cases. Therefore, it is important to be given provision regarding the psychology of marriage to the prospective bride and groom. The purpose of this service is to raise awareness of the nature of the prospective bride and groom and foster an understanding of a Sakinah, mawadah and merciful household from a psychological perspective. The method used is divided into 3 phases, namely Seminar and Discussion, Pocket Book on Marriage Psychology and Creating Whatsapp group and providing counseling to the group. The total number of participants was 44 people / 22 couples. The result of this service is that service participant members gain knowledge, understanding, and skills in dealing with and undergoing the marriage process and fostering their household. Abstrak. Pemberian layanan informasi psikologi perkawinan kepada peserta kursus sebagai calon pengantin di KUA Kecamatan Lubuk Kilangan Kota Padang, hal ini didasari oleh fenomena angka perkawinan yang cukup tinggi yaitu 40 pasang per bulan, dan indikasi perceraian setiap tahunnya mencapai 100 kasus. Oleh karena itu, penting untuk diberikan bekal mengenai psikologi pernikahan kepada calon pengantin. Tujuan dari pengabdian ini adalah untuk meningkatkan kesadaran akan fitrah calon pengantin dan menumbuhkan pemahaman tentang rumah tangga yang sakinah, mawadah dan rahmah dari segi psikologis. Metode yang digunakan terbagi menjadi 3 tahap yaitu Seminar dan Diskusi, Buku Saku Psikologi Perkawinan dan Membuat grup Whatsapp serta memberikan penyuluhan kepada kelompok tersebut. Jumlah peserta sebanyak 44 orang/22 pasangan. Hasil dari pengabdian ini adalah peserta pengabdian memperoleh pengetahuan, pemahaman, dan keterampilan dalam menghadapi dan menjalani proses perkawinan dan membina rumah tangganya.